Leisure, loafing, and life as work : discourses on non-work and a new working class - Bagarić, Petar, etnolog (Array, 2020)
Although leisure and idleness are promoted as a panacea for the problems of postmodern man, everyday logic of postindustrial societies is still subjected to the logic of “total work”. Throughout modernism, the discourse of leisure allowed for a certain separation of the worker from the work regime. However, this discourse lost its function in postmodernism due to the contemporary erasure of boundaries between life, work, and the self. The disappearance of these boundaries, due to technological development and newer forms of work organization, is an important element on the basis of which the contemporary middle class gradually assumes the position of the former working class within the system. Thus, it can be concluded that the fundamental way in which the avoidance of the world of total work is possible today is not leisure, free, fulfilled, and meaningful time, but shallow loafing, a stolen free moment otherwise scheduled for work.